Enhanced voltage generation through electrolyte flow on liquid-filled surfaces - B. Fan (Nature Portfolio, 2018)
Superhydrophobic surfaces are expected to increase streaming potential, but are hindered by the presence of air. Here the authors enhance streaming potential by flowing high-dielectric salt water over liquid-filled surfaces infiltrated with low-dielectric liquid, harnessing electric slip and surface charge.